2021
DOI: 10.1177/19433875211053760
|View full text |Cite
|
Sign up to set email alerts
|

Facial Trauma During the COVID-19 Pandemic

Abstract: Study Design Retrospective cohort study. Objective The purpose of this study is to evaluate the impact of the COVID-19 global pandemic on the regional trends in facial trauma at a tertiary care, level 1 trauma center in Central New York. Methods The study sample was derived from the population of patients who presented with facial trauma to the emergency department at the Downtown and/or Community Campuses of SUNY Upstate University Hospital between March 1, 2020, and May 15, 2020, and compared to two historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…For instance, with many recreational facilities and public spaces closed, people may be engaging in different types of activities at home, potentially leading to a shift in the causes of facial fractures. Similarly, the increase in work from home arrangements could potentially lead to a decrease injuries, including facial fractures [17][18][19]. This shift in epidemiology is clearly illustrated in the results of our study.…”
Section: Discussionsupporting
confidence: 54%
“…For instance, with many recreational facilities and public spaces closed, people may be engaging in different types of activities at home, potentially leading to a shift in the causes of facial fractures. Similarly, the increase in work from home arrangements could potentially lead to a decrease injuries, including facial fractures [17][18][19]. This shift in epidemiology is clearly illustrated in the results of our study.…”
Section: Discussionsupporting
confidence: 54%
“…When comparing the type of consults placed during COVID-19 surges with the historical data, an increased percentage was found to be inpatient consults when compared to consults placed from the ED. This finding corresponds with the decreased rate of ED visits during COVID peaks, which has been suspected to be a result of the culmination of public concern about exposure to COVID-19 infection, the implementation of strict social distancing guidelines, and the subsequently reduced rate of trauma [ 5 , 10 - 12 ]. No statistically significant differences were found in regard to the timing or weekday consultation rates.…”
Section: Discussionmentioning
confidence: 77%
“…Previously reported studies out of our institution demonstrated an increased otolaryngology consult volume in the years just prior to the current study. During the COVID-19 pandemic, another study found that the incidence of facial trauma presenting to our hospital decreased during the COVID-19 statewide lockdown orders but remained unchanged after these orders were lifted, but COVID-19 rates remained high in the region [ 10 ]. Decreased trauma and facial trauma rates during COVID-19 peaks are well documented in the literature and have been considered to be effects of social distancing and stay-at-home directives [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe Acute Respiratory Syndrome (SARS-CoV-2) is an infectious disease caused by COVID-19 which has negatively impacted the health system, causing changes in the epidemiological pattern of facial fractures, mainly in the incidence and etiology [ 12 ]. The COVID-19 pandemic led to the adoption of social restriction measures to isolate the community to mitigate the spread of coronavirus and differ according to the geographic area they occur.…”
Section: Introductionmentioning
confidence: 99%